2020
DOI: 10.1126/sciadv.abc5555
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal conductivity in low-angle twisted bilayer graphene

Abstract: Controlling the interlayer twist angle offers a powerful means for tuning the electronic properties of two-dimensional (2D) van der Waals materials. Typically, the electrical conductivity would increase monotonically with decreasing twist angle owing to the enhanced coupling between adjacent layers. Here, we report a nonmonotonic angle-dependent vertical conductivity across the interface of bilayer graphene with low twist angles. More specifically, the vertical conductivity enhances gradually with decreasing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 33 publications
(67 reference statements)
8
50
1
Order By: Relevance
“…The atomic structure was optimized until all force components are smaller than 0.5 meV/atom and the electronic calculations were then performed. The atomic structure relax- ation obtained by this method is shown to be in good agreement with experiments [18,[65][66][67] as well as the results obtained by other (both quantum and semi-classical) methods [60,[68][69][70], except that the intralayer equilibrium C-C bond distance is slightly overestimated by ∼ 1% [64].…”
Section: Introductionsupporting
confidence: 78%
“…The atomic structure was optimized until all force components are smaller than 0.5 meV/atom and the electronic calculations were then performed. The atomic structure relax- ation obtained by this method is shown to be in good agreement with experiments [18,[65][66][67] as well as the results obtained by other (both quantum and semi-classical) methods [60,[68][69][70], except that the intralayer equilibrium C-C bond distance is slightly overestimated by ∼ 1% [64].…”
Section: Introductionsupporting
confidence: 78%
“…However, note that when the twist angle between layers was rather small (generally less than 1°), atomic reconstruction could take place and was expected to have a profound effect on the band structures of the twisted bilayers 190 193 . In this case, the continuously varying rigid-lattice moiré pattern transformed to discrete commensurate domains divided by narrow domain walls, which had also been recently observed in twisted TMD vdW bilayers 194 , 195 .…”
Section: Interlayer Exciton Transport In Tmd Vdw Heterostructuresmentioning
confidence: 99%
“…All these works indicate that the diffusion barrier introduced by the moiré potential could be modified to affect exciton migration by tuning the twist angle or stacking mode between the constituent monolayers, which offers a novel way to control the exciton transport behavior in potential excitonic devices. However, note that when the twist angle between layers was rather small (generally less than 1°), atomic reconstruction could take place and was expected to have a profound effect on the band structures of the twisted bilayers [190][191][192][193] . In this case, the continuously varying rigidlattice moiré pattern transformed to discrete commensurate domains divided by narrow domain walls, which had also been recently observed in twisted TMD vdW bilayers 194,195 .…”
Section: Interlayer Exciton Transport Under Moiré Potentialsmentioning
confidence: 99%
“…This effect was reported for twisted bilayer graphene at "magic" stacking angles (    1 1 ), demonstrating intrinsic unconventional superconductivity, as well as renormalized vibrational and electronic structures [44,45]. Recent studies identified local atomic reconstruction up to a crossover angle of rigid twist at 5°, which results in abnormal electrical conductivity [46]. Our simulation results for a bilayer with     0 7 show that the moiré pattern selforganizes into a reconstructed triangular network by sacrificing the elastic deformation in graphene layers.…”
Section: Discussionmentioning
confidence: 71%